IMF Survey, Volume 32, Issue 05. (IMF Survey; IMF Survey ;, 2003)
Russia's unexpectedly strong recovery since its 1998 crisis has left people wondering whether it is just a temporary result of higher oil prices and the postcrisis depreciation of the ruble or a sign ofdurable improvements in the much-battered economy. This question is addressed in the book Russia Rebounds, written by members of the IMF's Russian team and due out later this year. John Odling-Smee, Director of the IMF's European II Department, spoke with Laura Wallace about Russia's prospects and its relationship with the IMF during the troubled 1990s. Odling-Smee, a U.K. national, joined the IMF in 1990 and took over responsibility for the IMF's relations with former Soviet Union countries in 1992. Before that, he served in the U.K. Cabinet Office and Treasury for about 15 years.